Natal Origin and Spatiotemporal Distribution of Leatherback Turtle (Dermochelys coriacea) Strandings at a Foraging Hotspot in Temperate Waters of the Southwest Atlantic Ocean - Vélez Rubio, Gabriela Manuela (2023)
Leatherback turtles migrate long distances between nesting beaches and distant foraging areas worldwide. This study analyzes the genetic diversity, life history stage, spatiotemporal distribution, and associated threats of a foraging aggregation in the Southwest Atlantic Ocean. A total of 242 leatherbacks stranded or bycaught by artisanal fisheries were recorded from 1997 to 2021 in Uruguay, with sizes ranging from 110.0 to 170.0 cm carapace lengths, indicating that the aggregation is composed of large juveniles and adults. Results of Bayesian mixed-stock analysis show that leatherbacks come primarily from the West African rookeries, based on mitochondrial DNA sequences obtained from 59 of the turtles representing seven haplotypes, including a novel one (Dc1.7). The main threat identified in the area is the fisheries bycatch but most of the carcasses observed were badly decomposed. There was significant seasonal and interannual variability in strandings that is likely associated with the availability of prey and the intensity of the fishing effort. Taken together, these findings reinforce the importance of these South American foraging areas for leatherbacks and the need to determine regional habitat use and migratory routes across the broader Atlantic region, in order to develop effective conservation measures to mitigate threats both at nesting beaches and foraging areas.